2018
DOI: 10.1002/srin.201800407
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Centerline Segregation on the Mechanical Performance and Microstructure of X70 Pipeline Steel

Abstract: Centerline segregation is an inherent phenomenon during solidification. It is controlled by optimizing the continuous casting process, but is not easy to be avoided. According to the severity of centerline segregation of the slab, it affects the mechanical properties and final microstructure of rolled strip. The objective of this paper is to study the influence of centerline segregation degree on the microstructure and mechanical properties of X70 pipeline steels. In this study, the mechanical properties of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The material used in this study is X70 pipeline steel, which chemical composition in weight percent (wt.%) is 0.045C-1.7Mn-0.1Si-0.41(Mo + Cr + Ni)-0.073(Nb + Ti)-0.012P-0.003S [20]. Two slabs and corresponding plates were studied in this paper and were named slab A and slab B, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The material used in this study is X70 pipeline steel, which chemical composition in weight percent (wt.%) is 0.045C-1.7Mn-0.1Si-0.41(Mo + Cr + Ni)-0.073(Nb + Ti)-0.012P-0.003S [20]. Two slabs and corresponding plates were studied in this paper and were named slab A and slab B, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies [6][7][8][9][10][11][12][13][14][15][16] suggested that centerline segregation decreases the mechanical performance of final products, such as: Low temperature toughness, weldability, and resistance to sour gas worsen; delamination fracture and band structure increase. References [17][18][19][20] suggested that control of centerline segregation in continuously cast slab can effectively improve low temperature toughness and elongation of pipeline steel. Because it is impossible to make the continuous casting continuous casting slab absolutely uniform, it is necessary to recognize the quantitative relationship between degree of segregation of slabs and the performance stability of plates.…”
Section: Introductionmentioning
confidence: 99%
“…This is related to the continuous casting production process. The centerline segregation can lead to local embrittlement [29].…”
Section: Hole Surface Evaluationmentioning
confidence: 99%
“…However, central carbon segregation along the casting direction occurs due to the carbon solubility difference between the liquid phase and solid phase, which can induce tremendous quality control issues in high-end steel products [1,2]. Moreover, this kind of defect is difficult to eliminate in reheating and rolling processes and will be left into the subsequent products, which will affect the tensile yield strength and low-temperature impact toughness [3,4]. Therefore, the control of central segregation along the casting direction is important to improve the quality stability of high-end steel products.…”
Section: Introductionmentioning
confidence: 99%